Documentary languages and knowledge organization systems in the context of the semantic web (Pesquisa Brasileira em Ciência da Informação e Biblioteconomia, 2014)
The aim of this study was to discuss the need for formal documentary languages as a condition for it to function in the Semantic Web. Based on a bibliographic review, Linked Open Data is presented as an initial condition for the operationalization of the Semantic Web, similar to the movement of Linked Open Vocabularies that aimed to promote interoperability among vocabularies. We highlight the Simple Knowledge Organization System format by analyzing its main characteristics and presenting the new standard ISO 25964-1/2:2011/2012 -Thesauri and interoperability with other vocabularies, that revises previous recommendations, adding requirements for the interoperability and mapping of vocabularies. We discuss conceptual problems in the formalization of vocabularies and the need to invest critically in its operationalization, suggesting alternatives to harness the mapping of vocabularies.Keywords: Documentary languages. Interoperability. Knowledge organization systems. Semantic web. Thesauri. VocabulariesLink para o texto completo (PDF)http://periodicos.puc-campinas.edu.br/seer/index.php/transinfo/article/view/1954/1750